(untitled) (International Journal of Medical and Surgical Sciences, 2015)
The Octodon degus, a rodent native to central Chile, in their natural habitat do not survive beyond 12 to 24 months, but in captivity reached an advanced age of 60 months on average. The research was conducted in six specimens of senile Octodon degus 48 to 66 months of age. The animals of this study were divided by age into the followingthree groups: group A 48 months 56 months group B and group C of 66 months. These individuals were born in captivity and fed ad libitum. They were studied in order to determine their histological characteristics. The penis was processed with the diaphanisation technique and subsequently for histology and stained with H-E, Masson staining and Von Kossa. In the senile penis bone, cartilage, fat, connective tissue compact parallel bundles, smooth muscle tendon fibers and nerve fibers can all be observed. The baculo showed the presence of several layers of osteoblasts, indicative of secretory activity of the extracellular matrix of bone. A contribution of this study found a tissue that maintains characteristics of undifferentiated blastema at very advanced ages of Octodon degus that allow to continually rebuild tissue. All these structures are dependent on testosterone and according to the results; the reproductive system of these animals was still working senility at the time, although with lower levels of testosterone than younger individuals. Octodon degus is a endemic rodent that has many reproductive strategies which continue over time despite their old age.